Does sunscreen use comply with official recommendations? Results of a nationwide survey in Germany. (12th December 2019) - Görig, T.; Schneider, S.; Seuffert, S.; Greinert, R.; Diehl, K.
Abstract: Background: The use of sunscreen can reduce the risk of UV‐induced skin lesions. Health authorities have provided recommendations for the correct use of sunscreen use: Sufficient amount of sunscreen should be applied at least 30 min before the sun exposure and should be reapplied every 2 h. Objective: We aimed to research the practice of sunscreen use in a population‐based and representative sample in Germany. Methods: For this cross‐sectional survey, 3000 German residents aged 14–45 years were surveyed in standardized telephone interviews in 2018. Survey participants provided data on the frequency of sunscreen use in summer, timing of (re‐)application and their skin characteristics. The data were weighted by age, sex, educational level and federal state to ensure the national representativeness of the sample. Results: Overall, 79.4% of respondents used sunscreen always, often or sometimes when being exposed to the sun. However, 87.2% of sunscreen users did not follow the recommendations on timing of application, 59.5% did not comply with the timing of reapplication. We also saw, that people potentially used too little sunscreen. These data did not differ noticeably by skin types of participants. Conclusion: Our study revealed deficits in use of sunscreen in Germany, indicating that people here pay little attention to the recommendations of health authorities, regardless of their skin type. There is therefore an urgent need for targeted public information on this issue. Improving public knowledge on correct sunscreen use through educational campaigns or individual counselling by health professionals could be a first step.